Menggagas “Sister City for Smart City” sebagai Optimalisasi Peran Hukum Internasional di Gorontalo - Mellisa Towadi; Waode Mustika (Jurnal Ilmiah Penegakan Hukum, 2022)
This study aims to provide policy recommendations in the legal context regarding regional needs for integrative problems so that the flexibility to open access to international cooperation is not only to promote regional potential but can empower that potential for sustainable development. The article was compiled using a juridical normative method supported by field data relating to the existing conditions in Gorontalo in terms of developing international law in the region, namely optimizing the role of the region in international relations as a consequence of the Regulation of the Minister of Foreign Affairs Number 3 of 2019 concerning General Guidelines for Foreign Relations by Local government. The results of the study indicate that strengthening diplomacy is part of the Gorontalo provincial government's efforts to get to know the personal identity of the region (regency and city) both in the context of local excellence and globally competent regional advantages and can even build future-oriented international relations. Sister cities or twin cities in the Gorontalo government will be one way to strengthen foreign diplomatic relations through international cooperation mechanisms that can enable the Gorontalo provincial government, both district and city, to play a strategic role to take advantage of the inter-governments/inter-federation state network. in other countries in order to realize the vision of good governance and the vision of a sustainable smart governance/smart city